The Use of Risk Assessment, Risk Management, and Engineering/Economic Feasibility Analysis in Remedial Decision Making for Contaminated Soils - E. J. Dorward-King; R. J. Kadeg; S. Pavlou (Society for Mining, Metallurgy & Exploration, 1992)
Risk assessment, risk management, and engineering/economic feasibility analysis are presented as three effective, practical tools for decision making in the remediation of contaminated soils. Risk assessment is applied to evaluate the extent, magnitude and sources of contamination, to identify appropriate contaminants of concern (COCs). Risk management is then applied to identify the acceptable contaminant residual levels for the COCs. Finally, engineering/economic feasibility analysis is used to define the appropriate cost-effective remedial action and associated target contaminant action levels that will achieve the acceptable contaminant residual levels. A real site application of this decision making approach is presented. This site illustrates that through appropriate engineering, acceptable risk-based contaminant residual levels can be achieved with higher action levels.